PENGEMBANGAN MODEL MODUL BERBASIS INKUIRI UNTUK PEMBELAJARAN MENYUNTING KARANGAN DI KELAS IX SMP NEGERI 2 SIROMBU KABUPATEN NIAS BARAT - Bimerdin Daely; Atmazaki .; Agustina . (Fakultas Bahasa dan Seni UNP, 2014)
Abstract: This research is aimed at describing the process of inquiry-based module design development on essay editing subject that is valid, practical, and effective in achieving the learning goal for class IX students of SMP Negeri 2 Sirombu Kabupaten Nias Barat. The type of this research is Research and Development/R&D with 4-D research design (define, design, develop, disseminate). This research uses quantitative approach. The data type of this research is quantitative data that consist of three types of data which are data validated by expert, data from practitioner’s assessments, and effectiveness data in form of learning results and student’s activities. Based on the result of the research, it reveals that the module design falls into category valid, practical, and effective. This could be seen in the validity of the module with a score of 90,41 which falls into very valid criteria. The practicality of teacher’s module is very practical with a score of 94,44 and the practicality of student’s module is 91,56 which falls into very practical criteria. The effectiveness of module, which consists of student’s learning results have average result of 81,05 which is qualified as Good (B) and the activities of students got a score of 81,48 with classification very active. Keywords: module, inquiry, essay edit